Visceral Leishmaniasis in Dogs - Silveira, Nathalia Saynovich Dutra; Mendes, Eduarda Mariana; Pereira, Marcy Lancia; Tavela, Alexandre de Oliveira; Veiga, Angela Patricia Medeiros; Zimermann, Francielli Cordeiro (Acta Scientiae Veterinariae, 2021)
Background: Canine visceral leishmaniasis (CVL) is a zoonosis of variable clinical presentation, either in systemic or cutaneous form. Clinical signs include anorexia, ophthalmopathies, and chronic kidney disease. In the state of Santa Catarina, the foci are concentrated in the capital and its adjacencies, in the east side of the state. The objective of this study is to outline the first three reported cases of CVL in the municipality of Curitibanos, since there are no reports to date in the region of the mountainous plateau, in the middle west of Santa Catarina. Cases: All dogs were treated at the Veterinary Clinic School of the Federal University of Santa Catarina, Campus Curitibanos. The animals, two males and one female, belonged to the same tutor, resided in Curitibanos, and were attended between 2016 and 2020. In the first case, attended in 2016, the complaint was of eye and skin changes about three months ago. The animal lived in an urban environment and came from Uruguaiana, Rio Grande do Sul. On physical examination, the animal presented skin peeling, wet and crusty lesions, bloody discharge in the ears and nasal hyperkeratosis, as well as signs suggestive of uveitis. In this case, euthanasia was carried out. The second case had complaints of respiratory, eye changes, hyporexia, and polydipsia. The dog was prostrate, dehydrated, with lymphadenomegaly and respiratory disorders, compatible with bacterial pneumonia. Bilateral corneal edema confirmed uveitis. Upon return, the animal remained dehydrated with enlarged lymph nodes. In the aspiration of the lymph nodes, suggestive forms of Leishmania sp. were observed. The recommended confirmatory tests were performed, leading to a definitive diagnosis of CVL. The patient was treated with miltefosine, but later died. The third case was attended for general evaluation after a positive diagnosis for CVL during an epidemiological survey of the second case. The animal was alert, tachycardic, and tachypneic with hyperemic mucous membranes. Miltefosine-based treatment and permanent use of deltamethrin-impregnated collar were prescribed and ovariohysterectomy was carried out. The patient is clinically well. In the search for vectors, in no place or moment of search, referring to the cases, vectors for CVL were found. Discussion: It is suggested that patients 2 and 3 are autochthonous cases, whose transmission form has not been fully elucidated, and vector transmission cannot be ruled out, as well as other less common forms of transmission. For case 1, it is suggested that it is an allochthone case, probably imported from the Uruguaiana region, where the disease is endemic. The conduct of a positive result for CVL is euthanasia, with the exception of dogs that have guardians who wish to perform treatment, but not always possible due to the high cost of miltefosine, the only drug approved for dog therapy in Brazil. In the first case, the owner opted for euthanasia, since in 2016 there was no possibility of treatment. For the last two cases, a treatment cycle was performed as recommended by the guidelines. Regarding the municipality of Curitibanos, in the first case diagnosed in 2016, the animal came from Uruguaiana. In conclusion, this study aimed to report the clinical and epidemiological characteristics related to the first three patients with CVL reported in Curitibanos.